Evaluación de la viabilidad de semillas en cinco variedades de maíz sometidas a envejecimiento acelerado - Entsakua Armijos, Jefferson Pedro (Machala : Universidad Técnica de Machala, 2021)
Corn is one of the most important cereals worldwide, with the United States being the largest producer of corn, in Ecuador corn is grown on a large scale especially in the provinces of Los Ríos, Manabí, Guayas and Loja, then determine the vigor of corn seeds is very important, so that our farmers do not have losses of great magnitude, it is emphasized that not everything depends on the vigor of a plant for its production, there are also other factors that can affect their performance, such as be the climate, soil, water quality, among others. The accelerated aging test was carried out in the plant health laboratory located at the Technical University of Machala, Faculty of Agricultural Sciences belonging to the province of El Oro, Machala canton, El Cambio parish, five varieties of seeds were used for the test of hybrid corn such as Trueno NB7443, Triunfo NB7253, Hercules, Dekalb 7080 and Advanta 9139 these varieties are very commercial nationwide, especially Trueno NB7443 which has a great acceptance in the producers of the province, four stratified samples of eighty seeds were taken for each variety of corn, giving a total of 20 samples that were distributed for the control and the treatments, therefore a T0: control for each variety, T1: treatment 1 in the same way for each variety, T2: treatment 2 will be repeated for each variety and T3: treatment 3 will also be performed for the five varieties, the methodology that was used for real Hoisting the test was subtracted from ISTA (International Seed Testing Association) for the most part, working with the highest temperature determined by ISTA in its range of 40ºC to 45ºC and with a relative humidity of 100%. The times for each test according to ISTA and the methodology consulted were 24h, 48h and 72h, it should be reiterated that a control was left to compare with the treatments. T0: 0h, T1: 24h, T2: 48h and T3: 72, after performing the accelerated aging test, a sowing of the seedlings was made to obtain variables such as Seed Color, Seed Shape, Leaf Length, Width of the leaf, Shape of the leaf, Weight of the root and Weight of the plant. The results were tabulated, two statistical tests Kolmogorow-Smirnov and Shapiro-Wilk were carried out, yielding a normality (<0.05 p-value), with their respective ANOVA of the time of exposure to heat giving significant differences between the varieties that were evaluated, I feel the T0 the highest point, this is due to the fact that it was not affected by the temperature, the TruenoNB7443 variety stands out in the weight of the plant that was not so affected by the temperature, the leaf length was more constant in the Advanta9139 variety, the width of the leaf it was noted that Advanta9139 again presented a constancy, while Hercules was affected, in the shape of the leaf no significant change was noticed due to the fact that the leaves are a similar characteristic in all varieties, the color of the seed It is a factor that did not have a great variation, especially in the Trueno NB7443, Dekalb 7080 and Advanta 9139 varieties, the seed shape was not affected by high temperature in no variety.
El maíz es un cereal de mucha importancia a nivel mundial, siendo Estados Unidos el mayor productor de maíz, en Ecuador el maíz se cultiva a gran escala sobre todo en las provincias de Los Ríos, Manabí, Guayas y Loja, entonces determinar el vigor de las semillas de maíz es de mucha importancia, para que nuestros agricultores no tengas perdidas de gran magnitud, se recalca que no todo depende del vigor de una planta para su producción, también existen otros factores que pueden afectar el rendimiento de estas, como puede ser el clima, el suelo, la calidad de agua, entre otros. El ensayo de envejecimiento acelerado se llevó a cabo en el laboratorio de sanidad vegetal ubicado en la Universidad Técnica de Machala, Facultad de Ciencias Agropecuarias perteneciente la provincia de El Oro, cantón Machala, parroquia El Cambio, para el ensayo se usaron cinco variedades de semillas de maíz hibrido como Trueno NB7443, Triunfo NB7253, Hercules, Dekalb 7080 y Advanta 9139 estas variedades son muy comerciales a nivel nacional, sobre todo Trueno NB7443 que tiene una gran aceptación en los productores de la provincia, se tomaron cuatro muestras estratificadas de ochenta semilla por cada variedad de maíz, dando en total 20 muestras que fueron distribuidos para el testigo y los tratamientos, por lo tanto queda dividido un T0: testigo para cada variedad, el T1: tratamiento 1 de igual manera para cada variedad, el T2: tratamiento 2 se volverá a repetir para cada variedad y el T3: tratamiento 3 también se realizara para las cinco variedad, la metodología que se utilizó para realizar el ensayo se sustrajo de ISTA (International Seed Testing Association) en su mayoría, se trabajó con la temperatura más alta que determina ISTA en su rango de 40ºC a 45ºC y con una humedad relativa de 100%. Los tiempos para cada en sayo según ISTA y la metodología consultada fueron de 24h, 48h y 72h, cabe reiterar que se dejó un testigo para comparar con los tratamientos. T0:0h, T1: 24h, T2: 48h y T3:72, luego de realizar el ensayo de envejecimiento acelerado se hizo una siembra de las plántulas para obtener variables como Color de Semilla, Forma de la Semilla, Largo de la Hoja, Ancho de la hoja, Forma de la hoja, Peso de la raíz y Peso de la planta. Los resultados fueron tabulados se realizó dos pruebas estadísticas Kolmogorow-Smirnov y Shapiro-Wilk arrojando una normalidad (< 0.05 p-valor), con su respectivo ANOVA del tiempo de exposición al calor dando unas diferencias significativas entre las variedades que se evaluaron, siento el T0 el punto más alto, esto se debe a no tuvo afectación por la temperatura, resalta la variedad TruenoNB7443 en el peso de la planta que no se vio tan afectado por la temperatura, el largo de hoja resulto más constante en la variedad Advanta9139, el ancho de la hoja se notó que nuevamente Advanta9139 presento una constancia, mientras que Hércules se vio afectado, en la forma de la hoja no se notó algún cambio significativo debió a que las hojas son una característica similar en todas las variedades, el color de semilla es un factor que no tuvo una gran variación sobre todo en las variedades Trueno NB7443, Dekalb 7080 y Advanta 9139, la forma de semilla no se evidencio afectada por la temperatura alta en ninguna variedad.
Keywords: ENVEJECIMIENTO; ACELERADO; VIGOR; GERMINACIÓN